1995
DOI: 10.1101/gad.9.23.2911
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial signaling by Sonic hedgehog and Wnt family members induces myogenic bHLH gene expression in the somite.

Abstract: We have demonstrated previously that a combination of signals from the neural tube and the floor platelnotochord complex synergistically induce the expression of myogenic bHLH genes and myogenic differentiation markers in unspecified somites. In this study we demonstrate that Sonic hedgehog (Shh), which is expressed in the floor platelnotochord, and a subset of Wnt family members (Wnt-1, Wnt-3, and Wnt-4), which are expressed in dorsal regions of the neural tube, mimic the muscle inducing activity of these tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
314
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(328 citation statements)
references
References 70 publications
12
314
0
2
Order By: Relevance
“…Chick embryonic tissue was cultured in type I collagen gels (Mü nsterberg et al, 1995) suffused with defined tissue culture medium: DMEM-F12 (Gibco), 5 r/ml human transferrin (Gibco), 100 r/ml conalbumin (Sigma), 1ϫ insulin-transferrin-selenium (Gibco), 1% Pen-Strep, and 1% L-glutamine. The cultures were incubated up to 24 hr (equivalent to the in vivo experiments) and fixed in 4% PFA.…”
Section: Microsurgery and Culturementioning
confidence: 99%
“…Chick embryonic tissue was cultured in type I collagen gels (Mü nsterberg et al, 1995) suffused with defined tissue culture medium: DMEM-F12 (Gibco), 5 r/ml human transferrin (Gibco), 100 r/ml conalbumin (Sigma), 1ϫ insulin-transferrin-selenium (Gibco), 1% Pen-Strep, and 1% L-glutamine. The cultures were incubated up to 24 hr (equivalent to the in vivo experiments) and fixed in 4% PFA.…”
Section: Microsurgery and Culturementioning
confidence: 99%
“…RT-PCR was performed as previously described 27 . The primers used for PCR amplification of ScShh (172 bp) were 5 0 -GAGCTGACAGGCTGATGACAC-3 0 and 5 0 -TGGTGATGTCCACAGCTCGGC-3 0 .…”
Section: Rt-pcrmentioning
confidence: 99%
“…Somite morphogenesis is closely linked to the progressive commitment of cells to adopt a particular fate, for example skeletal muscle, and both processes are governed and coordinated by networks of developmental signaling molecules that regulate gene expression (Buckingham, 2001). We have demonstrated, using somite explant cultures and reverse transcriptase-polymerase chain reaction (RT-PCR), that Wnt and Sonic hedgehog (Shh) signaling molecules, derived from the dorsal neural tube and notochord/floor plate, respectively, promote skeletal muscle specific gene expression and, thus, the myogenic differentiation program (Mü nsterberg et al, 1995;Schmidt et al, 2000). Recent work demonstrated that myotome-derived fibroblast growth factor (FGF) signals, acting through extracellular regulated kinase-mitogen-activated protein (ERK-MAP) kinase, specify a population of progenitor cells in the ventral somite, which gives rise to ribs and tendons (Smith et al, 2005).…”
Section: Introductionmentioning
confidence: 99%